FACTORS THAT INFLUENCE THE PURCHASE DECISION OF COSMETIC PRODUCTS ON FEMALE STUDENTS IN SURABAYA - Nadila Lazulfa Rohman; Ade Irma Suryani Lating; Eva Wany; Ajeng Tita Nawangsari; Mulyani Rahman Soulisa (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Having an attractive appearance is the main thing by society, especially for women who pay attention to beauty. With the development of technology is expected for the cosmetics industry to improve product quality and halal awareness given that indonesia is classified as the largest use of halal cosmetics in the world in order to compete in the business world to influence purchasing decisions. The purpose of this study is to prove the influence of fear of missing out, halal product quality awareness on cosmetic purchase decisions at UIN Sunan Ampel Surabaya students. This research data collection technique through questionnaires distributed online to UIN Sunan Ampel Surabaya students. The number of samples in the study of 67 respondents obtained through purposive sampling method. The results obtained that the fear of missing out does not have a significant effect on the decision to purchase cosmetic products at UIN Sunan Ampel Surabaya students because of budget factors and tend to buy as needed. While the quality of products and halal awareness has a positive and significant effect on cosmetic purchasing decisions at UIN Sunan Ampel Surabaya students because the better the quality of products and halal awareness, the higher the purchase decision